Characterization of aquatic humic substances to DBPs formation in advanced treatment processes for conventionally treated water - Hyun-Chul, Kim; Yu, Myong-Jin (ELSEVIER SCIENCE BV, 2007)
An advanced water treatment demonstration plant consisted of ozone/granular activated carbon processes was operated to study feasibility of the processes. Natural organic matter (NOM) from raw and process waters at the demonstration plant was isolated into humic and non-humic fractions by physicochemical fractionation method to investigate characteristics of humic fraction (i.e., humic substances, HS) as a predominant haloform reactant. Ozone did not significantly oxidize the carboxylic fraction (from 39.1 to 35.9%), while GAC removed some of the carboxylic fraction (from 35.9 to 29. 1 %). Formation potential of trihalomethanes (THMs) as compared to haloacetic acids formation potential (HAAFP) was highly influenced by HS. Higher yields of THMs resulted from chlorination of HS with a higher phenolic content and phenolic fraction in the HS gradually decreased from 60.5% to 15.8% through the water treatment. The structural and functional changes of HS were identified by elemental, Fourier-transform infrared (FT-IR) and proton nuclear magnetic resonance (H-1 NMR) analyses, and these results were mutually consistent. The functional distribution data obtained by using A-21 resin could be used to support the interpretation of data obtained from the spectroscopic analyses. Decreases in ratio of UV absorbance at 253 nm and 203 nm (A(253)/A(203)) and DBPFPs/DOC showed consistent trends, therefore, A253/A203 ratio may be a good indicator for the disinfection by-product formation potentials (DBPFPs). (C) 2006 Elsevier B.V. All rights reserved.
Keywords: DISSOLVED ORGANIC-MATTER; PREPARATIVE ISOLATION; NATURAL-WATERS; FRACTIONATION